Transnational bodies: Embodiment of transnational settings. Issue 1 (3rd May 2016) - Niekrenz, Yvonne; Witte, Matthias D.; Albrecht, Lisa
Abstract: The everyday life of more and more people is characterized by transnationalism. People increasingly interact across borders and in a network of transnational relationships. While interactions may be border-crossing, the actors' body remains situated and limited in time and space. However, the thesis of this paper is that transnationalism processes are embodied. Thus, we speak of an embodiment of transnational settings. We focus on symbolic interactionism – Charles H. Cooley and George H. Mead in particular provide a large repertoire of concepts – to theoretically conceive transnational bodies. To show how transnational embodiment can manifest itself we use the example of young people and their youth cultural life worlds. This offers an insight into the embodiment of standards and norms, such as ideals of beauty, that circulate transnationally, e.g. by the use of communication technologies.